Impact of Anxiety and Depression on Quality of Life among Patients Undergoing Hemodialysis: A Scoping Review - Fatima I. AlNashri; Hayfa H. Almutary; Elham A. Al Nagshabandi (Evidence-Based Nursing Research)
Context: Chronic kidney disease (CKD) is a life-threatening problem of global concern. Living with CKD is associated with many psychological problems, including depression and anxiety, which can directly or indirectly affect the quality of life. Only one review in the existing literature has assessed these associations among CKD patients using different dialysis modalities. However, the experience of these symptoms could be higher among patients on hemodialysis therapy. In this purview, there is a need to narrow the previous work to be more focused on hemodialysis patients.